2020
DOI: 10.1021/acs.biochem.0c00076
|View full text |Cite
|
Sign up to set email alerts
|

A Fluorogenic Molecule for Probing Islet Amyloid Using Flavonoid as a Scaffold Design

Abstract: sı Supporting InformationThe Supporting Information is available free of charge at https://pubs.acs.org/doi/10.1021/acs.biochem.0c00076.Characterization data of all flavonoid-based small molecules, all 1 H and 13 C NMR data, additional experimental details, fluorescence spectra, CD spectra, TEM images, docking analysis, and data for cytotoxicity tests (PDF)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Replacing hydroxyl groups with methoxy groups causes the compound to lose activity, suggesting the hydroxyl groups may be involved in the interaction with hA ( Velander et al, 2016 ). Furthermore, the flavonoid scaffold lacking any hydroxyl groups can bind with hA but does not inhibit fibrillation, suggesting the flavonoid core structure may interact with the hA peptide but that hydroxyl groups are required to prevent aggregation ( Chen, W. L. et al, 2020 ).…”
Section: Potential Mechanisms Of Actionmentioning
confidence: 99%
“…Replacing hydroxyl groups with methoxy groups causes the compound to lose activity, suggesting the hydroxyl groups may be involved in the interaction with hA ( Velander et al, 2016 ). Furthermore, the flavonoid scaffold lacking any hydroxyl groups can bind with hA but does not inhibit fibrillation, suggesting the flavonoid core structure may interact with the hA peptide but that hydroxyl groups are required to prevent aggregation ( Chen, W. L. et al, 2020 ).…”
Section: Potential Mechanisms Of Actionmentioning
confidence: 99%
“…44 Liu et al rationally designed probes using flavonoid as a scaffold and demonstrated that noncytotoxic 3-HF-ene-4′-OMe (Figure 3, 22) could detect islet amyloid polypeptide (IAPP) aggregates in living cells. 45 Nam et al developed a quinoline-based fluorescent probe (Q-tau 4, Figure 3, 23), that could be used as a tau-specific fluorescent imaging agent with lower background interference. 46 Yu et al present a novel, tau-selective, and AIE-active fluorescent probe (JL-3, Figure 3, 24), which demonstrated a remarkable capacity for bioimaging in living cells, brain tissues, and transgenic mice.…”
Section: Fluorescence Microscopy Utilizing Environment-sensitive Prob...mentioning
confidence: 99%
“…Mach et al designed a fluorescent α-syn probe (Tg-52, Figure , 21 ) with high affinity, discovering that α-synucleinopathies are conformationally different and display distinct small molecule binding sites . Liu et al rationally designed probes using flavonoid as a scaffold and demonstrated that noncytotoxic 3-HF-ene-4′-OMe (Figure , 22 ) could detect islet amyloid polypeptide (IAPP) aggregates in living cells . Nam et al developed a quinoline-based fluorescent probe (Q-tau 4, Figure , 23 ), that could be used as a tau-specific fluorescent imaging agent with lower background interference .…”
Section: Strategies Based On Optical Microscopymentioning
confidence: 99%
“…Monitoring early stage processes in protein aggregation is essential for the effective understanding and tackling of related neurodegenerative diseases, diabetes, and of other biological processes arising from protein misfolding leading to aggregation. , Beside the archetype thioflavin-T (ThT), other fluorescent dyes, , aggregation-induced-emission fluorogenic moieties (AIEgens), and luminescent conjugated oligomers and polymers (LCOs and LCPs) , have been proposed for monitoring the early stages of protein aggregation . Among these novel probes, LCOs and LCPs stand out due to the versatility of their structure, tailored to optimize the interactions with protein aggregates, with the most performing ones displaying a polyanionic character (multiple negatively charged carboxylates and/or sulfonates) and a hydrophobic backbone, yielding only partial water solubility.…”
Section: Introductionmentioning
confidence: 99%